Perancangan dan Implementası Jarıngan Wıreless Dormıtory Unıversıtas Internasıonal Batam - Stefanus Eko Prasetyo; Elvin Elvin (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
In this modern era, technology and information continue to develop in accordance with the development of human needs. One of them is the internet. The internet has many benefits, including as a means of communication, entertainment, and a source of information for education. To access the internet, a wireless network that is flexible, practical, and high mobility is needed. Students generally access the internet for their learning needs by using smartphones, laptops, and other devices through wireless network facilities at their residences and public places. Based on the results of a survey to the Batam International University dormitory, it was found that wireless network facilities did not yet exist. Therefore, it is necessary to install a wireless network in the Batam International University dormitory so that dormitory students can access the internet. This PkM activity is carried out through various stages, including the preparation stage, implementation stage, and evaluation stage. The result of this PkM activity is that dormitory students can connect to the installed wireless network and access the internet for learning and other needs.